A Survey of U.S. Prosthodontists and Dental Schools on the Current Materials and Methods for Final Impressions for Complete Denture Prosthodontics - Cynthia S. Petrie, DDS, MS;1 Mary P. Walker, DDS, PhD;2 (Journal of Prosthodontics, 2005)
The purpose of this study was to survey members of The American College of Prosthodontists (ACP) to evaluate current materials and methods for final impressions for complete denture prosthodontics in the United States